The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9082322
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Is Oral Implant Installation Using Surgical Guides Printed from a Degradable and Steam-Sterilized Biopolymer?

Abstract: 3D printed surgical guides are used for prosthetically-driven oral implant placement. When manufacturing these guides, information regarding suitable printing techniques and materials as well as the necessity for additional, non-printed stock parts such as metal sleeves is scarce. The aim of the investigation was to determine the accuracy of a surgical workflow for oral implant placement using guides manufactured by means of fused deposition modeling (FDM) from a biodegradable and sterilizable biopolymer filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
2
23
0
1
Order By: Relevance
“…However, another study using templates from different printers did not demonstrate any significant differences [ 38 ]. In a study on the influence of two different printing materials for templates, no significant differences were found [ 13 ]. An in vitro study by Henprasert et al showed that the fabrication of the template in an additive or subtractive process had no influence on the implant position [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study using templates from different printers did not demonstrate any significant differences [ 38 ]. In a study on the influence of two different printing materials for templates, no significant differences were found [ 13 ]. An in vitro study by Henprasert et al showed that the fabrication of the template in an additive or subtractive process had no influence on the implant position [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies regarding the accuracy of static navigation have identified influencing factors including intraoral positioning and fixation of templates [ 14 ]. The manufacturing process for the drill template can also impact the accuracy of implant placement, as can the materials used [ 15 , 16 , 17 ]. Several studies have reported the influence of different drill sleeves on accuracy [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three types of computer-generated surgical guides are currently available: supported by teeth, mucosa and bone. Tooth-supported guides are used in cases of partial edentulism [12].…”
Section: Drilling Guidementioning
confidence: 99%